Crystal buddies: inspiring stem interest through the magic of crystals / Siti Syaida Sirat - Sirat, Siti Syaida (Universiti Teknologi MARA, Negeri Sembilan, 2025)
In recent years, Malaysia has faced a growing challenge a noticeable decline in the number of students pursuing STEM (Science, Technology, Engineering, and Mathematics) subjects in schools. This concerning trend was highlighted in the article “STEM-ming the decline” published by The Star on 18 June 2023, which pointed to declining interest and the perception that STEM subjects are difficult, overly technical, and unapproachable. Many students find STEM intimidating, fearing that they may not succeed in subjects that seem too complex or demanding. This perception creates a significant barrier to nurturing the next generation of scientists, engineers, and innovators. Tackling this issue requires creative and engaging strategies to reconnect students with the wonders of science in a relatable and inspiring way.